Effect of disinfection agents and quantification of potentially viable Leptospira in fresh water samples using a highly sensitive integrity-qPCR assay. - Elise Richard; Pascale Bourhy; Mathieu Picardeau; Laurent Moulin; Sébastien Wurtzer (PLoS ONE)
Leptospirosis is an emerging worldwide zoonotic disease, but the general biology of the causative agents is still poorly understood. Humans are an occasional host. The main risk factors are water-associated exposure during professional or recreational activities or during outbreaks in endemic areas. Detecting the presence of pathogenic bacteria in aquatic environments and their capacity to resist various inactivation processes are research fields that need to be further developed. In addition, the methods used for detecting and enumerating Leptospira still need to be improved. We aimed to describe a new quantitative polymerase chain reaction coupled to propidium monoazide treatment (PMAqPCR) that targets not only total Leptospira but also discriminates pathogenic from non-pathogenic Leptospira while also addressing PCR inhibitors, a frequently encountered problem when studying environmental water. In a second step, the killing efficiency of Leptospira to different treatments was tested and PMAqPCR compared to culture-based enumeration. This provided information about the effects of temperature, as well as ultraviolet and chlorine disinfection, that are both related to water treatment processes, in particular for the production of drinking water, on the persistence of both saprophytic and pathogenic Leptospira. Finally, PMAqPCR was used for the detection of Leptospira in freshwater samples for a proof-of-concept. In conclusion, our method could be used for routine freshwater monitoring and allows better evaluation of the presence of Leptospira, allowing evaluation of the bacterial dynamics in a designated area or assessment of the efficacy of water disinfection processes.